Corporate and public governance in mining: lessons from the Marcopper mine disaster in Marinduque, Philippines - Lindon, John G (Archīum Ateneo, 2014)
The Philippines sits atop vast mineral deposits estimated to be worth around 47 trillion Philippine Pesos. Yet, mining in the Philippines has a mixed track record as far as its impact on human and economic development is concerned. This paper tries to draw lessons from the Marcopper Mine in Marinduque, Philippines, using a framework—what we call a “mining and human development causality chain”—to begin to think through how extractive industries can contribute to inclusive growth. Essentially, there is a chain of inputs and events that—when properly executed by various stakeholders—could lead to very strong economic and human development outcomes not just for the communities directly affected by the mine but also the country as a whole. Too often, this chain is easily broken by (both corporate and government) governance. Using a critical analysis of the Marinduque mining disaster, we illustrate how breaking this chain can completely reverse mining’s potential to assist in human development.